Understanding deafness, language, and cognitive development : essays in honour of Bencie Woll - Woll, B. (Bencie); Morgan, Gary, 1968- (Trends in language acquisition research, 2020)
"The study of childhood deafness offers researchers many interesting insights into the role of experience and sensory inputs on the development of language and cognition. This volume provides a state of the art look at these questions and how they are being applied in the areas of clinical and educational settings. It also marks the career and contributions of one of the deafness fields greatest scholars; Bencie Woll. As the deafness field goes through rapid and profound changes we hope this volume captures the latest understanding of this change on child development. The volume will be of essential interest to language development researchers as well as teachers and clinical researchers"--